Particularités des phénomènes de "floraison" - Mihnea, Pia Elena; Cuingioglu, Elvira (Cercetări Marine - Recherches Marines, 2026)
Some of the special conditions implied in the bloom phenomena are presented. Information on physical, chemical and biological conditions throughout 1975-1982, along the Romanian marine inshore waters are used. A comparison between the present state of phytoplanktonic community and the state that had existed twenty years ago, was made. The blooms of the most common species, the development of this phenomenon, and its dependence on physical and chemical factors are discussed. In high eutrophicated waters a stronger dependence of phytoplanktonic blooms by physical than common chemical factors (P-PO4, N-NO3) seemed to be obviously.